Tiros : weather eye in space weather eye in space - Jakes, John 1932 (New York : MacFadden, 1969)
T I R O S : Television Infra Red Observation Satelite
This edition is for readers for whom English is a second language. It can be anyone whos has learned 3,000 words of english.
Keywords: Satelite Artificial; Ingenieria Aeroespacial; Exploracion Del Espacio